Transfection of a rearranged viral DNA fragment, WZhet, stably converts latent Epstein-Barr viral infection to productive infection in lymphoid cells. - Grogan, E (1987)
An Epstein-Barr viral gene (ZEBRA) is identified that, in human lymphoblastoid cells, activates a switch causing the virus to shift from the latent to the replicative phase of its life cycle. We have shown that a 2.7-kilobase-pair rearranged Epstein-Barr virus DNA fragment of this gene (BamHI fragment WZhet) induced transient expression of viral replicative antigens and polypeptides when it was transfected into a somatic cell hybrid, which was derived from the fusion of an epithelial line cell with a Burkitt lymphoma cell. We now show that this rearranged WZhet fragment, when introduced stably into lymphoblastoid cells, will activate expression of the complete viral replicative cycle in 1-10% of the lymphoblastoid cells, leading to production of biologically active virions that can immortalize primary lymphocytes. The transfected plasmid appears to be regulated in a manner analogous to the complete Epstein-Barr virus genome.